Infeksi Protozoa Usus dan Anemia Sebagai Ancaman Kesehatan Global: Literature Review - Rahmah, Nisrina Nur; Mutiara, Hanna; Septiani, Linda; Himayani, Rani (CV. Jasa Sukses Abadi, 2025)
Intestinal protozoan infections are a global health issue that needs to be monitored due to the high morbidity and mortality rates, particularly in areas with poor hygiene and sanitation. Intestinal protozoan infections are diseases caused by protozoan parasites, which are single-celled eukaryotic microorganisms generally classified under the Kingdom Protista. The most frequently reported intestinal protozoa species responsible for human infections are Blastocystis hominis, Cryptosporidium parvum, and Giardia lamblia. There are two key factors contributing to the occurrence of intestinal protozoan infections: individual and environmental factors. Intestinal protozoan infections are known to cause various harmful consequences, particularly regarding the nutritional status of the affected individuals. As a result, intestinal protozoan infections are often associated with iron deficiency anemia, which can ultimately disrupt growth and development in children and decrease productivity in adults. This study aims to identify the pathways through which intestinal protozoan infections cause iron deficiency anemia. The study method involved a literature review and problem analysis. The results indicate that there are three main pathways through which intestinal protozoan infections lead to iron deficiency anemia: the metabolism of pathogenic microorganisms within the human body, the activation of the immune response to pathogenic microorganisms, and the reduction in micronutrient levels. To prevent these infections, the public is advised to improve personal hygiene, such as regularly washing hands, and to enhance environmental sanitation by treating water through filtration or disinfection.